Nitrogen removal enhanced by benthic bioturbation coupled with biofilm formation: A new strategy to alleviate freshwater eutrophication. (15th August 2021) - Yang, Wei; Yao, Jingmei; He, Yan; Huang, Yuyue; Liu, Huazu; Zhi, Yue; Qian, Shenhua; Yan, Xiaoman; Jian, Shuai; Li, Wei
Abstract: Excessive nitrogen input into the water caused eutrophication thereby reducing biodiversity and degrades freshwater function. Nitrogen pollution in sediments is one key reason that makes eutrophication difficult to control. The physicochemical technologies such as dredging and coverage for sediment pollution easily destroyed and homogenized aquatic habitats. To alleviate freshwater eutrophication in ecological way, this work combined the functions of bioturbation and biofilm to test their effect on the removal of nitrogen from sediment and water. The total nitrogen removal by employing the coupled function (bioturbation + biofilm, SCB) was greater than that of the single function (bioturbation or biofilm). The mean efficiency of total nitrogen removal in SCB treatment was 3.19 times that of the control without chironomids nor biofilm medium. Chironomid bioturbation promoted nitrogen release from sediments to the overlying water. Biofilm enhanced the conversion and removal of nitrogen stirred up by chironomids, resulting the lowest concentration of total nitrogen in overlying water of SCB treatment. The enhancement of nitrogen removal may be due to the coupled function increased the abundance of denitrifying and anammox functional bacteria in sediment and biofilm. Therefore, the method of combining benthic animals with biofilm medium is not only a viable solution for reducing sedimentary nitrogen loading in freshwater ecosystems, but also a solution to mitigate eutrophication in the overlying water. The restoration and management for aquatic ecosystems should consider protecting habitat for benthic organisms while maintaining heterogeneity for biofilm. Graphical abstract: Image 1 Highlights: Nitrogen removal was enhanced by benthic bioturbation coupled with biofilm formation. TN removal by chironomids and biofilm was 3.19 times that of the control system. Chironomid bioturbation promoted nitrogen release from sediments to the overlying water. Biofilm enhanced the conversion and removal of nitrogen stirred up by chironomids. System with chironomids and biofilm contains the richest abundance of bacteria for nitrogen removal.